2016
DOI: 10.1111/eva.12382
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the durability of plant resistance to aphids from a demo‐genetic study of Aphis gossypii in melon crops

Abstract: Resistance breakdown has been observed following the deployment of plant cultivars resistant to pests. Assessing the durability of a resistance requires long‐term experiments at least at a regional scale. We collected such data for melon resistance conferred by the Vat gene cluster to melon aphids. We examined landscape‐level populations of Aphis gossypii collected in 2004–2015, from melon‐producing regions with and without the deployment of Vat resistance and with different climates. We conducted demo‐genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…gossypii nuclear genome, as shown by its alleles for the SSR markers and CDSs characterized here. GEL6 was collected from cucurbits and observed on melon crops at different sites in France [55]. It had the biological features of clones specializing on cucurbits.…”
Section: Discussionmentioning
confidence: 99%
“…gossypii nuclear genome, as shown by its alleles for the SSR markers and CDSs characterized here. GEL6 was collected from cucurbits and observed on melon crops at different sites in France [55]. It had the biological features of clones specializing on cucurbits.…”
Section: Discussionmentioning
confidence: 99%
“…The cotton‐melon aphid, Aphis gossypii Glover, is a species that is increasing worldwide, colonizing more than 600 plant species (Blackman & Eastop, ). It causes serious economic losses in agriculture by feeding on plant foliage and spreading viral diseases in plants, such as cotton, cucurbits, and citrus (Thomas, Vanlerberghe‐Masutti, Mistral, Loiseau, & Boissot, ). It has been described as holocyclic in North China: eggs hatch in March and after two to three generations, late adults appear and move to cotton fields during late April to mid‐May.…”
Section: Introductionmentioning
confidence: 99%
“…Early season individuals on melon were alates, and so the entire potential colonizing population was sampled. Host plant pressure on aphids occurs in melons and aphid‐resistant melon cultivars and could alter the genetic structure of A. gossypii (Thomas et al., , ). In the present study, there was no known commercial aphid‐resistant melon varieties planted in the research area.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of landscape features on aphid dispersal have been documented (Angelella, Holland, & Kaplan, 2016;Gilabert et al, 2017). Thomas, Vanlerberghe-Masutti, Mistral, Loiseau, and Boissot (2016) conducted demo-genetic analyses of aphid populations on aphid-resistant plants during growth seasons and found that plant resistance changed the genetic structure of the aphid populations. Factors that modify the dispersal of founders may also modify the genetic composition of the population.…”
mentioning
confidence: 99%